The Hands-on Science Network science fair in Portugal - Esteves, Zita (2016)
The Hands-on Science Network organizes a major national science fair [1-3] in Portugal since 2011 [4]. Last year edition was held late May in Viana do Castelo in the northwest of Portugal. Being 2015 the International Year of Light, the main theme of the 5th HSCI Science Fair [5] was the light and optics and its applications. A good number projects from all fields of science were also presented. Nearly 150 projects enrolling over 450 students (Portuguese and Turkish – a large delegation of teachers from different regions of Turkey attended presenting 35 works on optics and ecology and environment coming from the project “Saving Our Species, S.O.S.”) were presented in a most lively science fair day that received over 500 visitors.